Herbarium specimens show patterns of fruiting phenology in native and invasive plant species across New England. Issue 1 (12th February 2018) - Gallinat, Amanda S.; Russo, Luca; Melaas, Eli K.; Willis, Charles G.; Primack, Richard B.
Abstract : Premise of the Study: Patterns of fruiting phenology in temperate ecosystems are poorly understood, despite the ecological importance of fruiting for animal nutrition and seed dispersal. Herbarium specimens represent an under‐utilized resource for investigating geographical and climatic factors affecting fruiting times within species, patterns in fruiting times among species, and differences between native and non‐native invasive species. Methods: We examined over 15, 000 herbarium specimens, collected and housed across New England, and found 3159 specimens with ripe fruits, collected from 1849–2013. We examined patterns in fruiting phenology among 37 native and 18 invasive woody plant species common to New England. We compared fruiting dates between native and invasive species, and analyzed how fruiting phenology varies with temperature, space, and time. Key Results: Spring temperature and year explained a small but significant amount of the variation in fruiting dates. Accounting for the moderate phylogenetic signal in fruiting phenology, invasive species fruited 26 days later on average than native species, with significantly greater standard deviations. Conclusions: Herbarium specimens can be used to detect patterns in fruiting times among species. However, the amount of intraspecific variation in fruiting times explained by temporal, geographic, and climatic predictors is small, due to a combination of low temporal resolution of fruiting specimens and the protracted nature of fruiting. Later fruiting times in invasive species, combined with delays in autumn bird migrations in New England, may increase the likelihood that migratory birds will consume and disperse invasive seeds in New England later into the year.